Three delay model: to find out the reason for maternal deaths - Agrawal, Neha; Patel, Seema; Badkur, Mayank (International Journal of Research in Medical Sciences, 2020)
Background: Each year in India, roughly 28 million women experience pregnancy and 26 million have a live birth. Of these, an estimated 67,000 maternal deaths and one million new-born deaths occur each year. A woman dies as a result of complication arising during pregnancy and childbirth every 90 seconds in the world, and every 7 minutes in India. The three delay model can be used to find the causes of delays in relation to maternal deaths. Methods: A retrospective study was carried out in a tertiary care centre. All cases of maternal mortality between July 2010 to June 2016 were included in the study. Then data analysis was done. Results: Out of the total 382 maternal deaths, Majority of maternal deaths 43% were due to type 1 delay. 150 patients had delay in seeking help, 9 patients refused treatment and 5 patients refused admission to health care centre. 13% maternal deaths were due to type 3 delay which include delay in receiving adequate treatment, Delay in diagnosis and intervention, Lack of facilities etc. Conclusions: Type-1 delay was major contributors of maternal deaths in the study region. Therefore, to prevent the preventable maternal deaths effective action should be taken.